2011
DOI: 10.1007/s10549-011-1704-y
|View full text |Cite
|
Sign up to set email alerts
|

FAN1 variants identified in multiple-case early-onset breast cancer families via exome sequencing: no evidence for association with risk for breast cancer

Abstract: We are interested in the characterisation of previously undescribed contributions to the heritable component of human cancers. To this end, we applied whole-exome capture, followed by massively parallel sequence analysis to the germline DNA of two greater than third-degree affected relatives from four multiple-case, early-onset breast cancer families. Prior testing for variants in known breast cancer susceptibility, genes in these families did not identify causal mutations. We detected and confirmed two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Several studies identified novel HBOC susceptibility genes like XRCC2 , FANCC and BLM [88,89,90,91,92,93]. Although it is feasible to apply WES and WGS in the near future as a generic test for every genetic diagnostic question, due to the costs (still high), the need of complex bioinformatics pipelines, of large storage capacity and the expected high number of VUS detected, today the clinical utility of mutation discovery throughout the complete exome or genome analysis is not convenient yet [91,94] and should be directed to specific patient groups [95].…”
Section: Inherited Cancer Syndromesmentioning
confidence: 99%
“…Several studies identified novel HBOC susceptibility genes like XRCC2 , FANCC and BLM [88,89,90,91,92,93]. Although it is feasible to apply WES and WGS in the near future as a generic test for every genetic diagnostic question, due to the costs (still high), the need of complex bioinformatics pipelines, of large storage capacity and the expected high number of VUS detected, today the clinical utility of mutation discovery throughout the complete exome or genome analysis is not convenient yet [91,94] and should be directed to specific patient groups [95].…”
Section: Inherited Cancer Syndromesmentioning
confidence: 99%
“…Furthermore, Huh et al [ 5 ] used exome sequencing to show that the c.234 G > A and c.1150C > T mutations in exon 18 of the HGSNAT gene were common in mucopolysaccharide patients. Exome sequencing techniques have also been used to understand the risks of various cancers, including those of the breast [ 6 7 ], prostate [ 8 ], pancreas [ 9 ], and others [ 10 11 12 ]. Therefore, exome sequencing techniques have become a new primary paradigm for research on genetic diseases and cancers.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the breast cancer exome studies reported so far failed to discover genes, whose significance is similar to BRCA1, BRCA2, CHEK2, PALB2, etc. [19][20][21][22]25,28,[132][133][134][135][136]. For example, Snape et al [133] subjected to WES 50 patients with familial breast cancer; they composed the list of promising candidates, but did not communicate yet the results of subsequent case-control study or segregation analysis.…”
Section: Breast Cancermentioning
confidence: 99%